Reframing: Strategi Konseling Kognitif untuk Mencapai Kebahagiaan Siswa Pasca Pandemi - Nawantara, Rosalia Dewi; Ramli, M. (Universitas Nusantara PGRI Kediri, 2023)
Happiness is something that every individual desires. Happy Feelings Refer to well-being of mental health. Not students at school. High academics that are not in accordance with abilities and good self-management can lead to unhappy conditions. Happiness (happiness) is synonymous with the term emotional well-being (EWB). Emotional well-being (EWB) or emotional well-being is an individual's state consisting of life satisfaction and positive feelings. The problem that occurs is that students feel less happy when they are at school because they do not immediately take perspective on a situation. For example, feeling that school is a place full of burdens, school is a boring place, and so on. The reframing technique is one of the techniques of cognitive therapy that aims to reorganize the desired emotional content and direct/reframe it towards a rational mind, so that the counselee can have various points of view on the self-concept/cognitive concept in various situations. This research method is literature study. Analysis of the data used is content analysis. The result of this research is the elaboration of theoretical studies on reframing techniques in cognitive therapy approaches that can be used to achieve students' emotional well-being.